(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
An investigation was carried out to provide an initial assessment of aquarium fish trade from December 2018 to May 2019 in Khulna city, Khulna of Bangladesh. A total 12 shops were established in this district where 46 aquarium fish species were found of which 12 species were bred for fry production. In the study area, some ornamental fishes such as Gold fish, Black moor, Comet, Red parrot, Tiger barb, Angel fish, Black molly, Guppy, koi carp, Rosy barb, Silver shark, Rainbow shark, Tiger shark, Sucker mouth catfish, Blue gourami, Pearl gourami, Golden gourami, White molly, Pearl scale gold fish, Silver dollar, LT sucker fish were very common. Besides Glass catfish, Siamese fighting fish, calico, Swordtail, Oscar, Widow tetra, Neon tetra, Balloon molly, Moon tail balloon molly, Alligator gar were common and Tangerrine swordtail, Arowana, Flower horn, Red tail black shark, platy, cardinal tetra, Discuss fish, Rummy nose, Bolivian ram, Balloon ram, Bosemoni rainbow, Red tail catfish, Bichir, Mono angel, Knife fish were the rare fish of the Khulna city. All aquarium fish species were brought from catabon area of Dhaka city that were mainly imported from the international markets like India, Singapore, Thailand, etc. Importers/wholesalers and breeders marketed them to retailers, local breeders, shopkeepers, etc. and finally, the shopkeepers sold them to the aquaria owners. The most profitable large aquarium fishes were Gold fish which made a profit of (100±20 tk/pair), Black moor (150±20 tk/pair), Red parrot (250±50 tk/pair), angelfish (100±10 tk/pair), Pearl gourami (300±50 tk/pair), Guppy (400±50 tk/pair), Siamese Fighting Fish (300±50 tk /piece), Tiger Shark (40±10 tk/pair), Sucker mouth catfish (50±5 tk/pair) to the retailers. During this survey, it was found that the breeders used cement tank, glass aquaria, plastic tank and even plastic jar as culture tanks. They bred aquarium fish all over the year. In the present study the market is mainly domestic. There is a good domestic market which is increasing day by day. Except winter, average annual income was recorded 13,140,000 Tk from the 12 aquarium shops. However, when temperature dropped during winter, sale became reduced; sometimes no selling was also observed during this time. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 142-153